2019
DOI: 10.3390/agronomy9060321
|View full text |Cite
|
Sign up to set email alerts
|

Grape Rootstock Response to Salinity, Water and Combined Salinity and Water Stresses

Abstract: Diminishing availability of non-saline water in arid and semiarid regions is of concern to all irrigated agricultural producers, including wine and grape producers. Grapes are not a salt tolerant crop and producers often face the choice of either limiting fresh water application, using alternative saline waters or a combination of both. We examined the salt tolerance and effect of restricted water application on three purported salt tolerant rootstocks grafted to Cabernet Sauvignon scion in a 4-year replicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Salinity stress is known to alter biosynthesis and accumulation of secondary metabolites like carotenoids [ 35 ]. Decrease in carotenoids of grapevine under salt stress might be due to induction of the pathway for abscisic acid production in order to modulate plant growth [ 32 ]. Increased carotenoids improve plant tolerance to stress condition due to quenching of ROS and preserving chloroplast from photo oxidation under stress conditions through their non-enzymatic antioxidant function [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salinity stress is known to alter biosynthesis and accumulation of secondary metabolites like carotenoids [ 35 ]. Decrease in carotenoids of grapevine under salt stress might be due to induction of the pathway for abscisic acid production in order to modulate plant growth [ 32 ]. Increased carotenoids improve plant tolerance to stress condition due to quenching of ROS and preserving chloroplast from photo oxidation under stress conditions through their non-enzymatic antioxidant function [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Grapevine ( Vitis vinifera L.) is considered as one of the most important, added-value agricultural products cultivated worldwide, consequently with significant economic importance [ 31 ]. Grapevine, relatively sensitive to salt stress, suffers significant losses in growth and productivity and also fruit quality under salinity conditions [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salinity damage is dependent upon the NaCl concentration, treatment time-course, and cultivar type. Several researchers have veri ed the mentioned side effects of salinity on plant 35,38 . Salinity impedes the vegetative and reproductive growth by the direct or indirect action on the physiological dynamics of cells and whole plants.…”
Section: Discussionmentioning
confidence: 99%
“…Guenette and Hernandez-Ramirez [12] evaluated the effect of soil compaction in conjunction with irrigation treatments in faba beans and found that maintaining high soil water content helps offset compaction damage. Suarez et al [13] evaluated the combined abiotic stresses of deficit irrigation and saline water on different wine (Cabernet Sauvignon) rootstocks. Unlike previous work, these researchers found that salinity stress does not reduce growth and ET further than drought stress alone at intermediate and severe deficit irrigations (less than 60% of the control), which is contrary to the FAO-56 model, where drought and salinity stresses are multiplicative.…”
Section: Et Under Different Cropping Systemsmentioning
confidence: 99%